2013
DOI: 10.1097/01.aoa.0000429113.02435.8c
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Hospital Obstetrical Volume and Maternal Postpartum Complications

Abstract: Objective-To examine the relationship between delivery volume and maternal complications.Study Design-We used administrative data to identify women admitted for childbirth in 2006. Hospitals were stratified into deciles based upon delivery volume. We compared composite complication rates across deciles.Results-We evaluated 1,683,754 childbirths in 1045 hospitals. Deciles 1 and 2 hospitals had significantly higher rates of composite complications than Decile 10 (11.8%, 10.1%, vs. 8.5%, P < .0001). Deciles 9 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…The overall rate of CD complications in the United States is generally reported to be <10%, based on nationwide hospitallevel data derived from billing codes. 11 Previous clinical studies have demonstrated that women who undergo a trial of labor after CD are at increased risk for adverse maternal outcomes compared with women who undergo repeat CD without a trial of labor. In addition to the rare but potentially catastrophic complication of uterine rupture, risks for transfusion and endometritis appear to be increased in this group.…”
Section: Smfm Papermentioning
confidence: 99%
“…The overall rate of CD complications in the United States is generally reported to be <10%, based on nationwide hospitallevel data derived from billing codes. 11 Previous clinical studies have demonstrated that women who undergo a trial of labor after CD are at increased risk for adverse maternal outcomes compared with women who undergo repeat CD without a trial of labor. In addition to the rare but potentially catastrophic complication of uterine rupture, risks for transfusion and endometritis appear to be increased in this group.…”
Section: Smfm Papermentioning
confidence: 99%
“…Maternal mortality is an uncommon event, and methods for tracking severe morbidity only have been proposed recently. 13 Data indicate that obstetric complications are significantly more frequent in hospitals with low delivery volume, 16 and that obstetric providers with the lowest patient volume have significantly increased rates of obstetric complications compared with highvolume providers. 17 Hospital clinical volume likely is a proxy measure for institutional and individual experience that may not be available at hospitals with lower volumes.…”
Section: Introductionmentioning
confidence: 99%
“…Delivery at hospitals with low delivery volumes has been correlated with better, worse and comparable pregnancy outcomes compared with delivery at larger centres, [1][2][3][4][5][6][7] and studies examining the safety of delivery at rural versus urban hospitals have likewise produced conflicting results. [8][9][10][11][12] Establishing the relative safety of obstetric care in small rural hospitals is challenging.…”
mentioning
confidence: 99%
“…[8][9][10][11][12] Establishing the relative safety of obstetric care in small rural hospitals is challenging. Studies comparing health outcomes according to hospital delivery volume [3][4][5] are influenced by underlying referral patterns in which higher rates of adverse outcomes at larger centres may reflect referrals of high-risk women. Adjustment for maternal risk factors is unlikely to completely account for case-mix differences.…”
mentioning
confidence: 99%